PRINSIP-PRINSIP MANAJEMEN PENDIDIKAN VS KINERJA GURU: SEBUAH TINJAUAN UMUM - Sola, Ermi (Educational Leadership: Jurnal Manajemen Pendidikan, 2021)
Abstract: Principles of Education Management VS Teacher Performance Management: an OverviewThe quality of education in each school is different. This happens because of different managerial strategies in managing school resources. Educational management is a series of activities carried out by a group of people who are members of educational organizations, to achieve predetermined educational goals, by utilizing existing resources and using management functions to achieve goals effectively and efficiently. The quality of the education and learning process can be viewed from two aspects, namely the quality of the components and the quality of school management. Although the supporting components such as the availability of adequate facilities and infrastructure, and sufficient funds, if they are not managed "well" and "properly" according to the education and teaching program (school program) that has been established, it can be ascertained that the objectives of education and teaching will not will be achieved effectively. For this reason, management principles are important instruments that can reveal the extent of the success or failure of teachers in achieving learning objectives and school programs. Abstrak: Prinsip-Prinsip Manajemen Pendidikan VS Kinerja Guru: Sebuah Tinjauan UmumKualitas pendidikan tiap sekolah berbeda-beda. Hal ini terjadi karena strategi manajerial yang berbeda dalam mengelola sumber daya sekolah. Manajemen pendidikan merupakan serangkaian kegiatan yang dilakukan sekelompok orang yang tergabung dalam organisasi pendidikan, untuk mencapai tujuan pendidikan yang telah ditetapkan sebelumnya, dengan memanfaatkan sumber daya yang ada dan menggunakan fungsi-fungsi manajemen agar tercapainya tujuan secara efektif dan efisien.  kualitas proses pendidikan dan pembelajaran dapat ditinjau dari dua segi, yaitu kualitas komponen dan kualitas pengelolaan sekolah. Walaupun komponen-komponennya penunjang seperti tersedianya sarana dan prasarana yang memadai, dan dana yang cukup, jika tidak dikelola dengan “baik” dan “tepat” sesuai program pendidikan dan pengajaran (program sekolah) yang telah ditetapkan,  maka dapat dipastikan tujuan pendidikan dan pengajaran tidak akan tercapai secara efektif. Untuk itu, prinsip-prinsip manajemen merupakan instrumen penting yang dapat mengungkap sejauh mana keberhasilan atau kegagalan para guru dalam pencapaian tujuan pembelajaran maupun program sekolah.